Tourniquet Use in Total Knee Arthroplasty - Arthur, Jaymeson R.; Spangehl, Mark J. (The Journal of Knee Surgery, 2019)
Tourniquet use in total knee arthroplasty has become a controversial topic. There are several benefits of its use including improved visualization, decreased blood loss, shorter operative times, and improved antibiotic delivery. Conversely, there are several significant downsides associated with tourniquet use including postoperative pain, neuromuscular injuries, wound complications, reperfusion injury, increased risk of thrombosis, patellar tracking issues, delayed rehabilitation including decreased postoperative range of motion, and its negative effect on patients with vascular disease. However, objectively, the literature does not definitively push us toward or away from the use of a tourniquet. Furthermore, several alternatives have been developed to help mitigate some of the adverse effects associated with its use. This article summarizes the evidence for and against tourniquet use and provides an evidence-based approach to help guide surgeons in their own practice.
Keywords: tourniquet; total knee replacement; total knee arthroplasty; TKA